Structural, magnetic and dielectric properties of two novel mixed-valence iron(ii)–iron(iii) metal formate frameworks. Issue 6 (14th January 2016) - Mączka, Mirosław; Ciupa, Aneta; Gągor, Anna; Sieradzki, Adam; Pikul, Adam; Ptak, Maciej
Abstract : Mixed-valence iron(ii )–iron(iii ) formate framework templated by diethylammonium cations exhibit structural and magnetic phase transitions near 240 and 39 K, respectively. Abstract : Two novel mixed-valence iron(ii )–iron(iii ) formate frameworks templated by ethylammonium and diethylammonium cations have been prepared and characterized by DSC, X-ray diffraction and spectroscopic methods. We also report dielectric and magnetic properties of the obtained samples. Both MOFs crystallize in the P 3̄1 c structure and exhibit magnetic order at 39 K. The analogue with diethylammonium cations undergoes a structural phase transition near 240 K into a triclinic phase. This transition has an order–disorder character and it is associated with pronounced dielectric anomaly. This compound is therefore the second discovered mixed-valence metal formate exhibiting multiferroic properties.